Meningkatkan daya saing Lontong : Pelatihan dan desain kemasan produk yang inovatif dan menarik - Utomo, Enggal Cahyo; Putri, Fifi Malinda; Adiantono, Muhammad Rizal; Nurubay, Ulfia; Putri, Wulan Setya; Trishananto, Yudha (Nur Science Institute, 2024)
Lontong is a traditional food that is popular in Indonesian society. However, Lontong is still less competitive than fast food. This community service aims to increase Lontong's competitiveness through training and innovative and attractive packaging design. The method used is training. The results of the community service show that training is necessary to standardize the quality and taste of Lontong. In addition, innovation in flavor variants and attractive and practical packaging designs will also increase Lontong's competitiveness. The training was conducted for 10 Lontong MSME actors in Pete Hamlet, Sukoharjo Village. The training materials include basic knowledge of design and assistance in practicing making packaging designs using applications. This activity increased participants' knowledge of utilizing simple digital applications to design more innovative packaging. It was concluded that training and creative packaging design can increase the competitiveness of traditional Lontong.